Current Concepts and Unresolved Questions in Dietary Protein Requirements and Supplements in Adults - Phillips, Stuart M. (Frontiers in Nutrition, 2017)
Protein needs for otherwise healthy individuals over 19 years of age are defined by the Recommended Dietary Allowance (RDA) at 0.80 g protein/kg/d. There is no recommendation in the current RDA for subpopulations of older adults or people in various pathological situations. Despite the lack of a separate recommendation, there exists a growing body of evidence that is strongly suggestive of an increased need and/or benefit for protein in older persons. That is, intakes beyond the RDA are, in older persons, associated with benefits. In addition, a number of catabolic states including critical illness also result in a sharp elevation in the needs for protein and amino acids. An underappreciated issue in protein nutrition is the impact of protein quality on clinically relevant outcomes. The introduction of a new protein scoring system – the digestible indispensable amino acids score (DIAAS) – for protein quality has raised a forgotten awareness of protein quality. The DIAAS, which replaces the protein digestibility-corrected amino acid score (PDCAAS), is based on ileal digestibility of protein and a different test protein than PDCAAS and has values greater than 1.0. The aim of this paper is a brief review and summary recommendations for protein nutrition and protein requirements in populations who would benefit from more protein than the RDA. The emphasis of the review is on muscle protein turnover, and there is discussion of the impact of protein quality, particularly as it applies to commercially available protein sources. The evidence for more optimal protein intakes is considered in light of the potential health risks of consumption of protein at levels greater than the RDA.